2013
DOI: 10.1093/cvr/cvt275
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin's lectin-like domain reduces myocardial damage by interfering with HMGB1-mediated TLR2 signalling

Abstract: The LLD of TM suppresses HMGB1-induced and TLR2-mediated myocardial reperfusion injury and apoptosis in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…Knockout of TLR4 in vitro or in vivo decreases HMGB1-induced tissue injury (Laird et al, 2014; Yang et al, 2013e; Ye et al, 2013a), cell migration and adhesion (Bauer et al, 2013) (Furlani et al, 2012; Wang et al, 2013m), angiogenesis (Lin et al, 2011), and the inflammation (Lv et al, 2009; Tadie et al, 2012b; Zong et al, 2013) and immunity responses (Apetoh et al, 2007). In addition to TLR4, TLR2 is required for tissue injury (Herzog et al, 2014; Kim et al, 2012h; Kruger et al, 2010; Leemans et al, 2009; Li et al, 2009), cell migration and adhesion (Furlani et al, 2012), inflammation (Park et al, 2006; Yu et al, 2006b), and self-renewal of stem cells (Conti et al, 2013). TLR9 is generally responsible for HMGB1-DNA complex-induced nucleotide immunity and RAGE can enhance this process (Bamboat et al, 2010; Hirata et al, 2013; Ivanov et al, 2007; Tian et al, 2007; Yanai et al, 2009).…”
Section: Hmgb1 Receptors (Figure 7)mentioning
confidence: 99%
“…Knockout of TLR4 in vitro or in vivo decreases HMGB1-induced tissue injury (Laird et al, 2014; Yang et al, 2013e; Ye et al, 2013a), cell migration and adhesion (Bauer et al, 2013) (Furlani et al, 2012; Wang et al, 2013m), angiogenesis (Lin et al, 2011), and the inflammation (Lv et al, 2009; Tadie et al, 2012b; Zong et al, 2013) and immunity responses (Apetoh et al, 2007). In addition to TLR4, TLR2 is required for tissue injury (Herzog et al, 2014; Kim et al, 2012h; Kruger et al, 2010; Leemans et al, 2009; Li et al, 2009), cell migration and adhesion (Furlani et al, 2012), inflammation (Park et al, 2006; Yu et al, 2006b), and self-renewal of stem cells (Conti et al, 2013). TLR9 is generally responsible for HMGB1-DNA complex-induced nucleotide immunity and RAGE can enhance this process (Bamboat et al, 2010; Hirata et al, 2013; Ivanov et al, 2007; Tian et al, 2007; Yanai et al, 2009).…”
Section: Hmgb1 Receptors (Figure 7)mentioning
confidence: 99%
“…Although high mobility group box-1 (HMGB1) has been suggested as important cardiomyocyte-derived alarmin[3], [4]; the identity of the key primary stimulus that may trigger the inflammatory reaction following infarction remains unknown. Using a combination of in vivo and in vitro approaches, Lugrin and co-workers[5] demonstrated that necrotic cardiomyocytes release Interleukin (IL)-1α, a key early damage signal that activates the abundant fibroblasts in the myocardium, promoting their pro-inflammatory activation through MyD88-dependent, toll like receptor (TLR)-independent signaling (Figure 1).…”
Section: Activation Of Pro-inflammatory Cascades Following Cardiac Inmentioning
confidence: 99%
“…Therefore, HMGB1 has been recognized as an important pro-inflammatory mediator and is important in initiating and amplifying the inflammatory response (912). In addition, it has been reported that the HMGB1-triggered inflammatory response is crucial in myocardial I/R injury since a decrease in HMGB1 expression and release could significantly inhibit the inflammatory response and ameliorate I/R-induced myocardial injury (11,33). Therefore, inhibition of the HMGB1-mediated inflammatory signaling pathway may be a promising therapeutic strategy for myocardial I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies demonstrated that extracellular HMGB1 is a potent pro-inflammatory mediator (9,10), and is important in triggering the inflammatory response during myocardial I/R (11,12). Furthermore, it has been reported that HMGB1 exerts its pro-inflammatory effects via its specific receptors, which mainly include a receptor for advanced glycation end products (RAGE), Toll-like receptor (TLR)-2 and TLR-4 (13).…”
Section: Introductionmentioning
confidence: 99%